War roads during the xixth century (2009)
Using travelers’ diaries and documents from the period as sources, the article presents the main war roads during the XIXth century. It emphasizes in their role as battle theaters and sources of economic and social capital. In an agrarian society as that of the XIXth century, roads represented territorial stri pes of geostrategic importance for battles. Political power sources and war spaces were located near such roads. In a time when war was mainly a war of positions, roads bordered not only economic structures, but also the geography of war. Special attention is given to the roads crossing the region of Valle and Cañón del Cauca delimited by Popayán’s high prairies and Batolito Antioqueño. The aforementioned region became a space containing warlike processes: Not only one of the most progressive economies of the nation was located there but also a war geohistoric space crisscrossed by a set of roads that facilitated the movement of armed actors through all of the national territory.